VALUE ADDED TO TAI LUE ETHNIC TEXTILE HANDICRAFT PRODUCTS IN NAYANG, LUANG PRABANG, LAO PDR. - SIRISACK, Dalivanh; INTHAJACK, Monsicha; TRAKANSIRIWANICH, Keerati; WAIAPHA, Yutthakarn (Asian Administration and Management Review, 2023)
The objectives of this research were to 1) explore the process of new product development of Tai Lue ethnic textile handicraft, 2) investigate value added of Tai Lue ethnic textile handicraft products, and 3) analyze the product development process that had influence on value added of Tai Lue ethnic textile. The sample group consisted of 400 Lao tourists who visited Nayang, Luang Prabang, Lao PDR. from January to May 2022. Findings showed that the product development processes had the highest mean score in screening and selection process, followed by idea generation, product development, product testing, and business analysis. For value added aspect, image value was found to have the highest average mean score, followed by personnel value, product value, and service value. According to NPD processes on ideas generation, business analysis, product development, and product testing stages, they showed a positive influence on the value-added, which could predict the value added of Tai Lue ethnic textile for 56.6%, while the screening and selecting process could not predict the value added of Tai Lue ethnic textile handicraft products for tourism with a statistical significance level of .05. The research suggested to the concerned parties should propose the model of product development to promote handicraft products of other communities, and the handicraft products should be promoted based on value added to support souvenir shops.